The more the merrier? The impact of longer high school on performance in college - Marcus Tamm; Katja Görlitz (Verein für Socialpolitik, 2010)
Following German reunification the East German states were confronted with the need to adapt their schooling system to quality criteria settled by the western states. Most importantly this included an extension of high school education by one year. We use this variation in high school duration to estimate the impact of years of schooling on choice of school degree, on attendance of college and on performance in college. The analysis is based on difference-in-differences estimates using variation in the timing of the reform between states.
Keywords: I21; I28; I00; 330; effects of schooling; educational performance; schooling reform